Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1073/pnas.0810813105
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of incommensurate crystal structure in Ca at high pressure

Abstract: Ca shows an interesting high-pressure phase transformation sequence, but, despite similar physical properties at high pressure and affinity in the electronic structure with its neighbors in the periodic table, no complex phase has been identified for Ca so far. We predict an incommensurate high-pressure phase of Ca from first principle calculations and describe a procedure of estimating incommensurate structure parameters by means of electronic structure calculations for periodic crystals. Thus, by using the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 25 publications
6
32
0
Order By: Relevance
“…5). This result is similar to that recently reported by Arapan et al (36), who found this structure by educated guess based on a possible analogy with Sr. Such Fig. 2.…”
Section: Results Of Evolutionary Simulations: New Phases Of Calciumsupporting
confidence: 82%
“…5). This result is similar to that recently reported by Arapan et al (36), who found this structure by educated guess based on a possible analogy with Sr. Such Fig. 2.…”
Section: Results Of Evolutionary Simulations: New Phases Of Calciumsupporting
confidence: 82%
“…At low pressure, our result is apparently different from the result by Arapan, Mao, and Ahuja. 26 In their results, sc Ca has the lowest enthalpy from 40 GPa to 77 GPa, lower than the P4 3 2 1 2 and Cmca structures. A possible reason is that the authors might not have taken into account the change in shape and internal coordinates of the Cmca structure in the 70-80 GPa pressure range.…”
Section: The Enthalpiesmentioning
confidence: 99%
“…Actually several other structures including Pnma, Cmca and P4 3 2 1 2 were proposed for the high pressure Ca-IV and Ca-V phases. 23,24,25,26 Their structural details are listed in Table I and their structures are pictured in reference [23,24,25]. I43m is a body-centered cubic structure, Pnma and Cmca Ca are orthorhombic, and P4 3 2 1 2 has a tetragonal symmetry.…”
Section: Theoretical Approach a Competing Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous computational studies have usually relied on the smallest possible commensurate approximants, although examples exist, for elementary and compound incommensurates, where the role of different host-guest ratios has been explored [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%